Hepatitis B and HIV coinfection in Northern Uganda: Is a decline in HBV prevalence on the horizon? - Annacarla Chiesa; Emmanuel Ochola; Letizia Oreni; Paolo Vassalini; Giuliano Rizzardini; Massimo Galli; Jason Blackard (PLoS ONE, 2020)
Background The available data concerning hepatitis B virus (HBV) infection in Uganda are limited, particularly in the case of people living with HIV/AIDS (PLWH). HBV is not routinely tested when starting antiretroviral therapy (ART). We aimed to determine the prevalence, the correlates of the risk of HBV infection, and the association with outcomes of ART among PLWH attending a busy HIV clinic in a referral hospital in Northern Uganda. Patients and methods From April to June 2016, a random sample of 1000 PLWH attending the outpatients’ clinic of St. Mary’s Hospital, Gulu, Uganda were systematically selected to undergo a rapid hepatitis B surface antigen (HBsAg) test after administering a questionnaire in this cross-sectional study. HIV care parameters were obtained from client files. Multivariate logistic regression and general linear model were used for the analysis. Results 950 of the 985 evaluable patients (77% females; mean age 42.8 years) were receiving ART. The overall prevalence of HBsAg was 7.9% (95% confidence interval [CI] 6.2–9.6%), and was significantly lower among the females (6.8% vs 11.7%; p = 0.020). The factors independently associated with higher HBV infection were having lived in an internally displaced persons’ camp (adjusted odds ratio [aOR] 1.76, 95% CI 1.03–2.98; p = 0.036) and having shared housing with HBV-infected people during childhood (aOR 3.30, 95% CI 1.49–7.32; p = 0.003). CD4+ T cell counts were significantly lower in HBV patients (p = 0.025), and co-infection was associated with a poorer CD4+ T cell response to ART (AOR 0.88; 95% CI 0.79–0.98; p = 0.030). Conclusions The observed prevalence of HBV among the PLWH may be underestimated or a signal of HBV decline in the region. The factors favouring horizontal HBV transmission identified suggest extending HBV screening and vaccine prophylaxis among PLWH.